Pengaruh NPM, ROA, DER dan Size terhadap Kinerja Keuangan pada Sektor Real Estate dan Property yang terdaftar di BEI Periode 2018-2020 - Sauh Hwee Teng; Paramita Rosadi Sitohang; Putri Citra Feronika; Ria Oktavia Damanik (Politeknik Ganesha Medan, 2022)
Good profit growth is an achievement expected by all companies. However, profit growth always fluctuates from time to time. This study aims to determine the effect of Net Profit Margin, Return On Assets, Debt To Equity Ratio and Size on Financial Performance in Real Estate and Property Companies. The samples used in this observation are from www.idx.co.id, which lists 16 companies from 52 sub real estate and properties companies registered in the BEI 2018-2020, 48 issuers over the last 3 years. The advanced sampling and its SPSS statistic software application v.20.0, using linear regression measures that indicate that coefficient determinations have a significant impact on net profit margin, return on assets, debt to equity ratio, the corporate size of Fcount 2.674 > Ftable 2.58. Based on the R Square value contained in this study, it shows that 18.2% of the variables Net Profit Margin, Return On Assets, Debt To Equity Ratio, Size and the remaining 81.8% are explained by other variables not examined in this study. Simultaneous testing shows, Net Profit Margins, Debt To Equity Ratios and Size have a significant effect on financial performance. The results of the partial hypothesis show that the Debt To Equity Ratio and Size have a negative and positive effect, while Net Profit Margin and Return On Assets have no significant effect on financial performance.